Embodying the Living Corpse: Intermedial Adaptation in Balinese "Calonarang" Shadow Theatre - I Made Marajaya; Ida Ayu Gede Sasrani Widyastuti (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
As Balinese Calonarang shadow theatre responds to shifting audience expectations and media influences, intermediality has emerged as a strategic mode of adaptation. This article examines a notable example: the emergence of the watangan matah or ‘living corpse,’ a figure performed by a live actor within the traditionally two-dimensional shadow space. This adaptation bridges symbolic shadow play with embodied presence, negotiating ritual integrity with theatrical spectacle. Using a mixed-method embedded design, the study combines descriptive quantitative data with ethnographic interpretation through observation, video analysis, interviews, and an audience survey. Findings show that the inclusion of watangan matah intensifies visual and emotional impact but generates divided responses between younger, media-oriented audiences and ritual purists. More significantly, staging a live corpse figure introduces power contestation, as puppeteers symbolically challenge mystical forces to assert spiritual authority. Watangan matah thus exemplifies how Calonarang theatre navigates preservation and transformation while maintaining its sacred resonance.